2017
DOI: 10.1155/2017/6297080
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Neuroprotective and Anti‐Inflammatory Effects of the Anthocyanin Metabolites, Protocatechuic Acid and 4‐Hydroxybenzoic Acid

Abstract: Anthocyanins are being increasingly investigated for their neuroprotective and antineuroinflammatory effects; however, the overall bioavailability of many anthocyanins is relatively low. In contrast, phenolic acids, metabolites of many polyphenols, including anthocyanins, have been shown to accumulate in tissue at higher concentrations than those of parent compounds, suggesting that these metabolites may be the bioactive components of anthocyanin-rich diets. We examined the neuroprotective capacity of two comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 57 publications
1
62
0
Order By: Relevance
“…In a total population based casecontrol study of individuals in Taiwan, aspirin use was found to have an inverse correlation to the incidence of ALS when controlling for confounders such as steroid use (Tsai et al, 2015). Other monophenolic acids, including structural isomers of the key active metabolite of aspirin, salicylic acid, have shown efficacy as anti-inflammatory and neuroprotective agents, with success specifically against hydrogen peroxide mediated damage (Winter et al, 2017).…”
Section: Aspirin Aspirin Derivatives and Combating Inflammationmentioning
confidence: 99%
“…In a total population based casecontrol study of individuals in Taiwan, aspirin use was found to have an inverse correlation to the incidence of ALS when controlling for confounders such as steroid use (Tsai et al, 2015). Other monophenolic acids, including structural isomers of the key active metabolite of aspirin, salicylic acid, have shown efficacy as anti-inflammatory and neuroprotective agents, with success specifically against hydrogen peroxide mediated damage (Winter et al, 2017).…”
Section: Aspirin Aspirin Derivatives and Combating Inflammationmentioning
confidence: 99%
“…PCA, one of the main metabolites of complex polyphenols, is a dihydroxybenzoic acid naturally found in green tea, and has strong free radical scavenging effects. PCA displays numerous biological activities, including anti-oxidant, anti-atherosclerotic, anti-apoptotic, anti-inflammatory, and neuroprotective activity [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. PCA was reported to be significantly more concentrated and with longer retention in plasma than other polyphenol compounds, and can pass through the blood brain barrier (BBB) easily [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Forni et al, 2019). most phytochemicals, components of food, beverages, and herbal products are often reported in literature as "nutraceutical", emphasizing their health promoting properties, including the prevention and treatment of pathologies like cancer, cardiovascular diseases, neural disorders, and Alzheimer's disease (Winter et al, 2017). The phytochemical analysis of EST showed that the extract is found to be rich in phlobatannins, carbohydrates, alkaloids, terpenoids and flavonoids, which attribute to its biochemical activities and properties.…”
Section: Resultsmentioning
confidence: 99%